Risk Analysis of Obstructive Sleep Apnea and Mental Disorders with Self-Reporting Questionnaire (SRQ-20) in Hospitalized COVID-19 Patients - Falyani, Silvy Amalia; Pratiwi, Suryanti Dwi; Sugiri, Yani Jane Rosihaningsih; Djajalaksana, Susanthy; Listyoko, Aditya Sri (Universitaas Brawijaya, 2025)
Introduction: Obstructive Sleep Apnea (OSA) is closely related to diseases such as hypertension, diabetes, cardiovascular disease, and obesity. Evaluation of sleep disorders and mental health in COVID-19 patients who are hospitalized has not been widely studied. The purpose of this study was to analyze the risk of OSA with STOP-Bang and mental disorders with the Self-Reporting Questionnaire (SRQ-20) in hospitalized COVID-19 patients at RSUD dr. Saiful Anwar Malang. Case: Thirty five respondents with confirmed mild and moderate COVID-19 criteria randomly selected and agreed to give informed consent were given the STOP-Bang and SRQ-20 questionnaires, then the score was associated with the oxygenation ratio through blood gas levels. The research was conducted by cross sectional and statistical test using Chi Square and Mann Whitney test with p<0.05. Thirty five respondents were divided into two groups, 17 people (48%) with mild criteria and 18 people (52%) with severe criteria. The severity of COVID-19 had low effect on the risk of OSA (p=0.581) and mental disorders (p=0.191). The risk of mental disorders through SRQ-20 scoring had low effect on the severity of COVID-19 (p=0.229) and on the oxygenation ratio (p=0.068). Conclusion: The severity of COVID-19 and oxygenation ratio had low effect to the risk of OSA and mental disorders through the STOP-Bang and SRQ-20 scores in hospitalized COVID-19 patients at dr. Saiful Anwar Malang.